CELEBRATING SCIENCE: THE E³UDRES² Science Festival 2025 as a Platform for Professional Growth and Networking in Higher Education - Potomkina, Nanuly; Jurane-Bremane, A.; Bilyk, Olena (ХДАК, 2025)
In the context of global educational transformation, international academic mobility has become a key indicator of teaching quality and professional excellence. Modern universities view international staff exchanges as strategic tools for institutional development, pedagogical innovation, and integration into the European Higher Education Area. The Erasmus+ Staff Mobility Programme plays a pivotal role, offering educators opportunities to develop professional skills, adopt innovative teaching methods, and engage in intercultural communication. Active involvement in Erasmus+ provides access to global collaboration networks and the co-creation of educational innovations. The partnership between Kharkiv State Academy of Culture (KhSAC, Ukraine) and Vidzeme University of Applied Sciences (Vidzemes Augstskola, Latvia) is a sustainable commitment to excellence in teaching, research, and international academic dialogue. As part of this collaboration, the scientific and pedagogical staff of KhSAС participated in the global academic mobility Programme (BIP identifier: 2024-1-LV01-KA171-HED-000229621).
Keywords: міжнародна діяльність ХДАК; Харківська державна академія культури; Kharkiv State Academy of Culture; академічна мобільність